IMMUNOMODULATORY EFFECT OF OYSTER GLYCOGEN ON ENDOMETRITIC CROSSBRED COWS - BISWAL, SHUVRANSHU SH; DASH, S; MOHANTY, D N (The Indian Journal of Animal Reproduction, 2023)
The purpose of the study was to evaluate the immunomodulatory effect of intrauterine infusion of oysterglycogen on endometritic cows. 500mg of oyster glycogen reconstituted in phosphate buffer saline (PBS) wasgiven as intrauterine infusion to cows of group I (n=10) during estrus. In second group (n=10) normal estrus cowswithout any treatment formed as control. Cervical mucus sample was collected aseptically and sent to laboratoryfor bacterial culture and count.Polymorph nuclear (PMN) cell count from uterine fluid showed a significant elevation(13.14 ± 1.35vs.73.71 ± 3.59) before and after24hrs. of treatment. Serum globulin, albumin: globulin ratio, aspartateaminotransferase (AST), haptoglobin and serum amyloid A (SAA) values before treatment were significant (p
Keywords: Oyster glycogen; lmmunomodulator; Endometritis; Acute phase proteins